Village Budget Use for Infrastructure: Case of Beringin Jaya, South Baebunta, North Luwu - Jam’an, Andi; Asdar, Asdar; Fiqrizal, Fiqrizal (Jurnal Ekonomi Balance, 2025)
This study aims to analyze the utilization of the Village Budget (APBDes) for infrastructure development in Beringin Jaya Village, South Baebunta District, North Luwu Regency, and to identify the key factors affecting its effectiveness. A mixed-methods approach was employed, combining both quantitative and qualitative data, primarily drawn from the 2022 Village Budget documents. The data were analyzed using qualitative techniques, including data reduction, presentation, and verification. The results indicate that the allocation of the Village Budget significantly contributes to improving community welfare through infrastructure development. However, several challenges hinder its effectiveness, particularly in the planning, implementation, and monitoring phases. These challenges include limited financial resources, misalignment between infrastructure projects and community needs, low levels of community participation, and environmental threats such as flooding. To enhance the effectiveness and sustainability of rural infrastructure development, this study recommends improving village governance, promoting inclusive and participatory planning, and strengthening disaster risk mitigation strategies. These measures are essential to ensure that infrastructure development is both impactful and resilient in the long term.